A Hospice-Based Bereavement Support Group Using Creative Arts: An Exploratory Study. (October 2015) - McGuinness, Breffni; Finucane, Niamh; Roberts, Amanda
There is evidence of the value of individual creative arts (art, drama, music, etc.) in helping people to cope with bereavement. However, there is a gap in the research on the effectiveness of the intentional, combined use of creative arts activities in bereavement support group intervention for adults. This article describes an exploratory study which assessed the effectiveness of using creative arts activities in an eight session support group intervention. A waiting list, randomized control trial supplemented by limited qualitative data was used. Evidence was found that the intervention did help participants' ability to move between loss and restoration coping when they attended at least six of the eight sessions. However, the use of creative arts activities appears to be more suitable for some people than for others.